The settlement system of the Republic of Tuva: central places - Sitkovskiy, Arseniy M.; Delovarova, Leila F. (The New Research of Tuva, 2025)
The article presents an analysis of the settlement framework of the Republic of Tuva. The methodological basis includes statistical research methods and geoinformation methods (such as schematic mapping and the isochrone method). Data preparation and processing were carried out using MS Excel and MS Power BI; cartographic visualizations were created using Yandex DataLens and EverGis. The data sources comprised local history materials, the 2010 All-Russian Population Census, and estimated population data in settlements as of 2020.A methodology for identifying the “settlement framework” is proposed, which in this case is understood as a network of the most demographically stable settlements. The methodology enabled the identification and visualization of the settlement framework of the Republic of Tuva. It includes one “medium-sized city”— Kyzyl — and its 12 peripheral settlements, 15 central places, and 78 adjacent settlements. The result is presented as a schematic map. Zones of 60-minute transport accessibility from all 16 centers of the “settlement framework” were analyzed and visualized.The study also identified and analyzed significant discrepancies between the official list of “central” and “adjacent” settlements of the Republic of Tuva and the results of this research and proposes recommendations for revising the former.The proposed methodology may serve as a tool for informed decision-making in setting priorities for the financing and modernization of key settlement centers.
Keywords: rural area; settlement system; demographic dynamic; settlement framework; central place; adjacent settlement; Republic of Tuva